FUNGSI SINTAKTIS DAN PERAN SEMANTIS ARGUMEN INTI BAHASA MANGGARAI DIALEK MANGGARAI TENGAH - Albertina Yosefina Samu (Masyarakat Linguistik Indonesia, 2018)
This study examines the syntactic functions and the semantic roles of core arguments in Central Manggarai Dialect of Manggarai Language (CMDML). There are two theories applied in this study, i.e., Lexical- Functional Grammar and Macro Roles. This research uses qualitative method. The source of data is Manggarai language texts in oral and written forms. The results show that the basic structure of verbal clauses in CMDML are S+P+O, P+O+S, S+P+O+Oθ, S+P+COMP, P+COMP+S,P+S+COMP and non-verbal clauses are S+P, P+S. The syntactic functions of core arguments in CMDML are Subject (SUBJ), Object (OBJ) and Object Teta (OBJθ). The semantic roles of core argument in CMDML are devided into two, macroroles and thematic roles. Macroroles consist of Actor and Undergoer, while thematic roles consist of Agent, Experiencer, Effector, Recipient, Theme, Source dan Patient.